A comparison of endogenous and microbial proteolytic activities during fast fermentation of silver carp inoculated with Lactobacillus plantarum. (15th September 2016) - Yang, Fang; Xia, Wen-Shui; Zhang, Xiao-Wei; Xu, Yan-Shun; Jiang, Qi-Xing
Highlights: The roles of different proteases during fast fish fermentation were determined. Lactobacillus plantarum from fish had low proteinase activities. Gel strength was mainly weakened by endogenous lysosomal proteases. Lactobacillus plantarum led to pleasant taste and volatile compounds precursors. Abstract: The study was aimed to investigate different roles of endogenous and Lactobacillus plantarum proteases during fast fermentation of silver carp. The results show that endogenous proteases could degrade both sarcoplasmic and myofibrillar proteins. In contrast, L. plantarum had low proteinase activities and could only hydrolyze sarcoplasmic peptides. This indicates that gel properties could be mainly affected by endogenous proteolysis while microbial proteolysis contributed to the production of smaller peptides and free amino acids which may be related to flavor and taste. Texture and free amino acid analyses verified these hypotheses. It shows that endogenous lysosomal proteases were the major contributors for the decrease of gel strength while L. plantarum proteolytic activities could lead to the increase of aspartic acid, glutamic acid, and alanine, which may result in umami and sweet taste; and also lead to a rise in some amino acids which were volatile compounds precursors.